PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP KOMPETENSI PROFESIONAL GURU DI SMK NEGERI SE-KOTA PADANG - Anggreeny, Desi; Ayu Ningrum, Tia; Sulastri; Widiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of teachers' professional competence in improving the quality of learning and the need for principals' academic supervision as a professional development effort for teachers. This study employed a quantitative approach using an associative method. The population consisted of 635 teachers from public vocational high schools (SMK Negeri) in Padang City, with a sample of 254 teachers selected using the Stratified Proportional Random Sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and simple linear regression with IBM SPSS Statistics version 26. The findings indicate that teachers' professional competence was in the good category with a respondent achievement level of 81.40%, while principals' academic supervision was also in the good category with a respondent achievement level of 82.47%. The study further revealed that principals' academic supervision had a positive and significant effect on teachers' professional competence. These findings indicate that effective academic supervision contributes to improving teachers' professional competence. Therefore, principals are expected to continuously optimize the implementation of academic supervision in a planned, sustainable manner and provide appropriate follow-up based on teachers' needs.